2008
DOI: 10.1002/msj.20038
|View full text |Cite
|
Sign up to set email alerts
|

Predictive genetic testing in minors for adult‐onset genetic diseases

Abstract: This article analyses the ethical discussion of predictive genetic testing in minors for genetic conditions for which there is no phenotypic evidence for disease at the considered time of testing and for which there is currently no treatment available to prevent or forestall the development of the condition. After a presentation of the position of various professional guidelines, we discuss the position and arguments that have been advanced in a recent article that defends a position that is opposed to the pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
56
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(58 citation statements)
references
References 31 publications
(24 reference statements)
2
56
0
Order By: Relevance
“…Unless there were pressing medical reasons for testing, all 27 papers proposed that one should postpone testing until the child could consent. There are few reports concerning predictive testing in minors for adultonset conditions (Borry et al 2008;Wade et al 2010), and it is important to investigate whether young persons benefit from the information such testing yields, and whether risk information causes psychosocial harm to young persons genetically tested for AIP.…”
Section: Previous Researchmentioning
confidence: 99%
“…Unless there were pressing medical reasons for testing, all 27 papers proposed that one should postpone testing until the child could consent. There are few reports concerning predictive testing in minors for adultonset conditions (Borry et al 2008;Wade et al 2010), and it is important to investigate whether young persons benefit from the information such testing yields, and whether risk information causes psychosocial harm to young persons genetically tested for AIP.…”
Section: Previous Researchmentioning
confidence: 99%
“…1 Presymptomatic genetic testing of minors (under the age of 18 years) is not usually recommended unless effective clinical actions are available. [2][3][4] Generally, there are three key arguments against presymptomatic genetic testing in adolescents or young people: that it (1) fails to respect the future autonomy of the young person; (2) breaches confidentiality; and (3) may cause psychosocial harms. 5 The age at which young people should undergo presymptomatic genetic testing for adult-onset disorder is a matter of debate.…”
Section: Introductionmentioning
confidence: 99%
“…5 The age at which young people should undergo presymptomatic genetic testing for adult-onset disorder is a matter of debate. [2][3][4][5] Key challenges have to be faced during the transition from adolescence to adulthood, such as marriage, finishing education, beginning full-time employment and becoming a parent, and the impact of testing may affect, and be affected by each of these events. In the light of the above-mentioned issues, it would be appropriate to ask what health information and counselling young adults need to make prudent decisions about genetic testing.…”
Section: Introductionmentioning
confidence: 99%
“…With respect to the presymptomatic and predictive genetic testing of children, in general, guidelines recommend that the availability of therapeutic or preventive measures are necessary for testing to be performed in asymptomatic minors. 26,27 In order to protect the privacy and confidentiality of genetic information and the minor's right not to know, it is suggested that testing asymptomatic children when there is no urgent medical need, be postponed until a minor can participate in the decision-making process. 26,27 We have previously studied the issue of DTC GT for health-related traits in children by conducting a content analysis of DTC GT companies' websites.…”
Section: Introductionmentioning
confidence: 99%
“…26,27 In order to protect the privacy and confidentiality of genetic information and the minor's right not to know, it is suggested that testing asymptomatic children when there is no urgent medical need, be postponed until a minor can participate in the decision-making process. 26,27 We have previously studied the issue of DTC GT for health-related traits in children by conducting a content analysis of DTC GT companies' websites. 20,21 In our most recent study, results showed that of the 29 companies studied; almost a third of companies perform genetic testing in minors upon parental request.…”
Section: Introductionmentioning
confidence: 99%